Career Development in Military Court - Ginting, Sri Ulina; Rahmadani, Vivi Gusrini; Zulkarnain, Zulkarnain (Journal of Business Management and Economic Development, 2024)
Career development is an employee's point of view that provides an overview of future career paths in the organization and signifies the long-term interests of the organization to employees. In developing employee careers, organizations need to provide good support regarding information, training, and opportunities that will have a positive impact on the organization. This study aims to determine the level of employee career development at the Military Court in Medan Indonesia. The sampling technique was total sampling with a sample size of 76 people. Data collection was done through questionnaires. This study used One-Way ANOVA and cross tabulation. The results of this study concluded that career development in the Military Court is in the high category. Career development of military employees is high and career development in government employees is low. This study can be a guideline for organizations to see the level of employee career development and invest in improving career development.